DETERMINAN NILAI PERUSAHAAN PADA INDUSTRI ELECTRONIC GAMING DAN MULTIMEDIA - Rayhan Adha (2021)
The aim of this research is to analyze determinant of firm value, which is profitability, firm size, and leverage on Electronic Gaming and Multimedia Industry. The sample of this study are 12 companies of Electronic Gaming and Multimedia Industry classified by ychart.com and listed on NASDAQ. The sampling method used is purposive sampling. This type of research is a quantitative study using Data Panel Regression as analytical techniques with 5% level of significance. The result of this research showed that profitability and firm size have no effect on firm value. While leverage has a significant effect on firm value.